Gastric pH and Toxin Factors Modulate Infectivity and Disease Progression After Gastrointestinal Exposure to Bacillus anthracis. (15th September 2017) - Xie, Tao; Rotstein, David; Sun, Chen; Fang, Hui; Frucht, David M
Abstract : Using a murine gastrointestinal anthrax model, we demonstrate that survival of vegetative B anthracis is only partially diminished by gastric acid. Anthrax lethal toxin is required for systemic infection, whereas edema toxin modulates the progression and pattern of dissemination. Abstract: Gastrointestinal (GI) anthrax is the most prevalent form of naturally acquired Bacillus anthracis infection, which is associated with exposure to vegetative bacteria in infected meat (carnivores) or to fermented rumen contents (herbivores). We assessed whether key host and pathogen factors modulate infectivity and progression of infection using a mouse model of GI infection. Gastric acid neutralization increases infectivity, but 30%–40% of mice succumb to infection without neutralization. Mice either fed or fasted before exposure showed similar infectivity rates. Finally, the pathogen's anthrax lethal factor is required to establish lethal infection, whereas its edema factor modulates progression and dissemination of infection.